A Cross-Sectional Study of Maternal Near Miss Events and Maternal Deaths Using the Operational Guidelines of the Government of India 2014 - Lakra, Pinkey; Sangwan, Vijayata; Kaushik, Jaishree; Shivani, Shivani; Siwach, Sunita (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVE: Maternal near miss (MNM) events share many pathological and circumstantial factors with maternal mortality. Compared with maternal mortality, near-miss events are more common; thus, MNM evaluation is used to assess the quality of obstetric care in a health facility. STUDY DESIGN: This is a prospective, observational, cross-sectional study of critically ill women admitted to the intensive care unit, using the operational Guidelines of the Government of India 2014. Maternal deaths during this period were also reviewed. The MNM-to-mortality ratio, MNM incidence ratio, and maternal mortality index were determined, along with the identification of MNM and maternal mortality causes and risk factors. Data on demographics, obstetric history, underlying disorders leading to ICU admission, lifesaving interventions performed, and treatment delays were collected and analysed. RESULTS: There were 7,669 deliveries and 7,222 live births. Sixty-six cases were diagnosed as MNM, and there were 17 maternal deaths. The incidence of MNM was 9.13 per 1,000 live births. The MNM-to-mortality ratio was 3.8:1. The maternal mortality ratio was 142 per 1,00,000 live births. The three leading complications in MNM were haemorrhage (50%), hypertensive disorders of pregnancy (31.8%), and sepsis (10.6%). Level 1 delay was present in 57.5% of cases, followed by level 3 delay in 51.5% of MNM cases. CONCLUSIONS: Haemorrhage and hypertensive disorders of pregnancy remain the leading cause of MNM and mortality.